Implicit detection of change: Can we do without awareness? - Norvilas, A.; C., Miller J. (Psichologija, 2010)
D. Fernandez-Duque and I. M. Thornton (2000) seemingly demonstrated “unconscious detection of change” (p. 338), i.e. a person being able to register stimulus change without being aware of it. However, as the authors themselves point out, their experiment might harbor a potential flaw: the failure to include a control condition. In a series of two experiments, we tested participants’ ability to detect change, while not being aware of it, both in the absence and in the presence of a control condition. With the control condition absent, both experiments failed to replicate D. Fernandez-Duque and I. M. Thornton’s finding of an increase in change detection for unaware trials. With the control condition present, change detection did exceed the chance level. We argue that a correlated conscious strategy hypothesis offers a better account of the change detection results for unaware trials than the unconscious change detection hypothesis.